Edge Loading and Wear Risk Analysis of a Marine Water-Lubricated Stern Bearing Considering Shaft-Deflection-Induced Journal Tilting - Xianyi Li; Jingjun Lou; Zhimin Chen; Maoting Tan; Ming Yang; Binbin Qiu; Haibo Wan (Journal of Marine Science and Engineering, 2026)
Classical hydrodynamic lubrication studies of journal bearings routinely invoke two simplifying assumptions: the axially rigid–straight journal assumption and the structure–lubrication decoupling assumption. For marine water-lubricated stern bearings, propeller overhung loading induces non-negligible shaft deflection across the bearing length, and the multi-support shafting makes the stern-bearing reaction force impossible to determine from rigid-body statics alone. Both assumptions must be removed within a single analysis framework. This study develops a coupled lubrication–rotor framework that combines a two-dimensional steady Reynolds solver with groove masking, a Winkler elastic liner, and a ROSS-based Timoshenko rotor finite element model through bidirectional reaction-force–tilt feedback. A normalised axial load distribution indicator Iw(z), defined from the axial film-pressure profile, is introduced as a scalar boundary quantity linking the elastohydrodynamic lubrication solution to downstream wear evolution models. Condition decomposition and open-loop tilt sweeps show that the coupled-convergence tilt reduces hmin by 65.7%, raises pmax by 84.5%, and shifts the axial reaction-force distribution and Iw(z) peak toward the stern end. Axial non-uniformity intensifies monotonically with the increase in tilt angle, and beyond a threshold tilt, the HD/EHL solver no longer converges for a hard phenolic liner, establishing the applicability upper bound of the framework.